2021
DOI: 10.3390/vaccines9111281
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an LSDV-Vectored Vaccine for Heterologous Prime-Boost Immunizations against HIV

Abstract: The modest protective effects of the RV144 HIV-1 vaccine trial have prompted the further exploration of improved poxvirus vector systems that can yield better immune responses and protection. In this study, a recombinant lumpy skin disease virus (LSDV) expressing HIV-1 CAP256.SU gp150 (Env) and a subtype C mosaic Gag was constructed (LSDVGC5) and compared to the equivalent recombinant modified vaccinia Ankara (MVAGC5). In vitro characterization confirmed that cells infected with recombinant LSDV produced Gag v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…The effect of adjuvanting the DNA vaccines with CpG oligodeoxynucleotide (ODN) 1826 combined with Stratis delivery was found to further improve the immune response, with 10 out 15 rabbits developing binding antibody responses to HIV Env after a single DNA vaccination and all of them after two DNA vaccinations. Similar results were seen in other studies by this group when DNA vaccines were administered IM using Stratis both with and without CpG [ 88 , 89 ]. Overall, these studies showed that the immunogenicity of DNA vaccines delivering HIV antigens was significantly improved when delivered using NFIS as compared to NS.…”
Section: Nfis Delivery Of Dna Vaccines For Pandemic Virusessupporting
confidence: 90%
See 3 more Smart Citations
“…The effect of adjuvanting the DNA vaccines with CpG oligodeoxynucleotide (ODN) 1826 combined with Stratis delivery was found to further improve the immune response, with 10 out 15 rabbits developing binding antibody responses to HIV Env after a single DNA vaccination and all of them after two DNA vaccinations. Similar results were seen in other studies by this group when DNA vaccines were administered IM using Stratis both with and without CpG [ 88 , 89 ]. Overall, these studies showed that the immunogenicity of DNA vaccines delivering HIV antigens was significantly improved when delivered using NFIS as compared to NS.…”
Section: Nfis Delivery Of Dna Vaccines For Pandemic Virusessupporting
confidence: 90%
“…Dr. Williamson’s group at the University of Cape Town has developed DNA vaccines expressing HIV Gag virus-like particles and envelope (Env), which have been tested in rabbits using heterologous prime–boost regimens ( Table 2 ) [ 89 ]. Rabbits were inoculated with two DNA primes followed by two to four poxvirus-vectored boosts and, in some studies, two HIV envelope protein boosts.…”
Section: Nfis Delivery Of Dna Vaccines For Pandemic Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…A putative non-essential gene encoding a G-protein-coupled chemokine receptor subfamily homologue has been tested as a site for homologous recombination [ 103 ]. The region between the convergent LSDV open reading frames (ORFs) 49 and 50 have also been used without gene disruption [ 20 , 104 , 105 ].…”
Section: Introductionmentioning
confidence: 99%